Energetics of best performances in track cycling - Capelli, C.; Schena, F.; Zamparo, P.; dal Monte, A.; Faina, M.; Di Prampero, P. E. (Medicine & Science in Sports & Exercise, 1998)
VO2max and best performance times (BPTs) obtained during maximal voluntary trials over 1, 2, 5, and 10 km from a stationary start were assessed in 10 elite cyclists. Steady-state VO2 and peak blood lactate concentration ([La]b) were also determined in the same subjects pedaling on a track at constant submaximal speeds.